Interior Regularity Results for Fractional Elliptic Equations That Degenerate with the Gradient - Topp-Paredes, E (Academic Press, 2021)
In this paper we obtain interior regularity estimates for viscosity solutions of nonlocal Dirichlet problems that degenerate when the gradient of the solution vanishes. Interior Hölder estimates are obtained when the order of the fractional diffusion is less or equal than one, and Lipschitz estimates when it is bigger than one. In the latter case, the estimates are robust enough to conclude interior C1,α regularity by an improvement of the flatness procedure, which is possible when the nonlocal term is close enough to a second-order diffusion. © 2021 Elsevier Inc.